INOVASI PEMBELAJARAN ABAD 21: SOSIALISASI PEMBELAJARAN MENDALAM (DEEP LEARNING) UNTUK MENINGKATKAN KOMPETENSI GURU - Baharuddin, Baharuddin (Universitas Islam 45 Bekasi, 2025)
This study aims to describe the effectiveness of a community service program in the form of a socialization and workshop on Deep Learning in improving teacher competency in the Muhammadiyah community, Malang. The challenges of education in the digital era require teachers to adopt innovative learning methods that go beyond memorization. Therefore, this activity was designed to equip 20 teachers with conceptual understanding and practical skills. The program was implemented over three days, focusing on theoretical presentations, practical preparation of deep learning-based Lesson Plans (RPP), and evaluation and reflection. Quantitative data from the pre-test and post-test instruments showed a significant increase in participant understanding, with the average score increasing from 61.5 to 87.45. Qualitative analysis of the feedback questionnaire also showed that 98% of participants found the material useful and 95% felt more motivated. These findings prove that a hands-on and structured approach is effective in changing teachers' teaching paradigms. The conclusion of this program is that the socialization of deep learning is a strategic step to improve the quality of education and empower teachers to be able to create relevant and immersive learning experiences for students, in line with the vision of 21st-century education.